(untitled) (In situ, 2025)
The paper presents the results of archaeological excavations at the Bronze Age site of Gradina in Turanj, conducted during 2024. This year’s research was focused on a part of the ramparts along the western side of the entrance to the hillfort, where, within the outer face of the rampart, two graves with four deceased persons, mostly children, were discovered. One of the aforementioned graves also contained numerous metal accessories, and, as it seems, amber beads, which is an extremely rare find in northern Dalmatia. Also, burials in fortification structures have not been recorded in Dalmatia in the context of Bronze Age settlements, and this phenomenon is rarely documented in the wider Adriatic area. In addition, another trial trench within the settlement (trial trench 5) was investigated, which showed an identical stratigraphic and cultural picture as the other previously investigated trial trenches.